Cross-cultural validity of Morningness-Eveningness Stability Scale improved (MESSi) in Iran, Spain and Germany. (7th February 2017) - Rahafar, Arash; Randler, Christoph; Díaz-Morales, Juan F.; Kasaeian, Ali; Heidari, Zeinab
ABSTRACT: Morningness-Eveningness Stability Scale improved (MESSi) is a newly constructed measure to assess circadian types and amplitude. In this study, we applied this measure to participants from three different countries: Germany, Spain and Iran. Confirmatory factorial analysis (CFA) of MESSi displayed mediocre fit in the three countries. Comparing increasingly stringent models using multigroup confirmatory factor analyses indicated at least partial measurement invariance (metric invariance) by country for Morning Affect and Distinctness subscales. Age was positively related to Morning Affect (MA), and negatively related to Eveningness (EV) and Distinctness (DI). Men reported higher MA than women, whereas women reported higher DI than men. Regarding country effect, Iranian participants reported highest MA compared to Spaniards and Germans, whereas Germans reported higher DI compared to Iranians and Spaniards. As a conclusion, our study corroborated the validity and reliability of MESSi across three different countries with different geographical and cultural characteristics.